MiR-130a regulates neurite outgrowth and dendritic spine density by targeting MeCP2. Issue 7 (1st June 2016) - Zhang, Yunjia; Chen, Mengmeng; Qiu, Zilong; Hu, Keping; McGee, Warren; Chen, Xiaoping; Liu, Jianghong; Zhu, Li; Wu, Jane Y
Abstract: MicroRNAs (miRNAs) are critical for both development and function of the central nervous system. Significant evidence suggests that abnormal expression of miRNAs is associated with neurodevelopmental disorders. MeCP2 protein is an epigenetic regulator repressing or activating gene transcription by binding to methylated DNA. Both loss-of-function and gain-of-function mutations in the MECP2 gene lead to neurodevelopmental disorders such as Rett syndrome, autism and MECP2 duplication syndrome. In this study, we demonstrate that miR-130a inhibits neurite outgrowth and reduces dendritic spine density as well as dendritic complexity. Bioinformatics analyses, cell cultures and biochemical experiments indicate that miR-130a targets MECP2 and down-regulates MeCP2 protein expression. Furthermore, expression of the wild-type MeCP2, but not a loss-of-function mutant, rescues the miR-130a-induced phenotype. Our study uncovers the MECP2 gene as a previous unknown target for miR-130a, supporting that miR-130a may play a role in neurodevelopment by regulating MeCP2. Together with data from other groups, our work suggests that a feedback regulatory mechanism involving both miR-130a and MeCP2 may serve to ensure their appropriate expression and function in neural development.